Effect of Feed Form, Corn Particle Size, and Extrusion of Corn on Broiler Performance - Marut Saensukjaroenphon; Caitlin E. Evans; Cassandra K. Jones; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2022)
The pelleting and extrusion processes use both thermal and mechanical energies to alter the crystalline structure of the starch granule, which makes it more digestible than raw starch. The particle size of the ground corn particle in the diet also affects the rate at which gelatinization occurs in the extrusion process. There is limited research on broiler performance when feeding diets that contain different particle sizes of corn prior to extrusion. The objective of this study was to determine the effect of feed form, corn particle size and the extrusion of corn on growth performance of 21-d-old broiler chicks. To determine the effect of corn type on growth performance, treatments were arranged in a 2 × 3 factorial of corn type (raw corn and extruded corn) and corn particle size (400, 800, and 1200 μm). There was no interaction (P>0.742) between corn type and corn particle size on d 21 BW, ADFI, or feed conversion ratio (FCR). Broilers fed the raw corn diet had greater (P<0.001) d 21 BW and ADFI compared to those fed the extruded corn diets. There was no evidence of difference (P>0.081) in d 21 BW and ADFI in broilers fed the three different corn particle sizes. Broilers fed diets with increasing corn particle size had increased (linear,P= 0.015) FCR. There was an interaction (P<0.039) between corn type and corn particle size on both the relative gizzard and pancreas weights of broilers. To determine the effects of feed form on growth performance and relative gizzard and pancreas weight, treatments were arranged in a 2 × 2 factorial of feed form (mash and crumble feed) and corn particle size (400 and 800 μm). There was no evidence of interaction (P>0.180) between feed form and corn particle size on growth performance or relative gizzard and pancreas weight. Broilers fed the crumble extruded corn diet had increased (P= 0.001) d 21 BW and ADFI compared to those fed the mash extruded corn diets. There was no evidence of difference (P>0.189) in d 21 BW, ADFI, and FCR between broilers fed extruded diets containing 400 μm corn and 800 μm corn regardless of feed form. Broilers fed the mash extruded corn diet had greater (P<0.001) relative gizzard and pancreas weights as compared to those fed the crumbled extruded corn diets. In addition, broiler relative gizzard weight was greater (P= 0.002) for those fed the extruded corn diet containing 800 μm versus 400 μm corn, while there was no evidence of difference in relative pancreas weight. Therefore, increasing the amount of gelatinized starch in the feed by replacing ground corn with extruded corn in a broiler starter diet did not improve growth performance. Increasing corn particle size led to improved gizzard development.
Keywords: corn; extrusion; particle size; pelleting; poultry